MANAJEMEN SANGGAR SENI BU'DEWI PRODUCTIONDI KABUPATEN PADANG PARIAMAN - Aulia, Hia; Syeilendra (Universitas Negeri Padang, 2025)
This research aims to describe the organisational management at Sanggar Seni Bu'dewi Production, which has four functions: planning, organising, mobilising, and monitoring, located in Nagari Sicincin, Padang Pariaman Regency. This study uses qualitative descriptive methods with data collection techniques including observation, interviews, and documentation. The results indicate that the organisational management of Sanggar Seni Bu'Dewi Production encompasses four main functions: planning, organising, mobilising, and monitoring. Planning is carried out through deliberation by the leaders and management, organisation is shown through a clear organisational structure, mobilisation is done through motivation and regular training, and supervision is conducted directly by the leaders. This structured and collaborative management plays a crucial role in maintaining the existence of the studio, enhancing the productivity of artistic works, and strengthening the role of the studio as a centre for the preservation of local culture.